The Influence of Stress Management and Public Speaking through Academic Achivement - Nurul Husna (International Student Conference on Business, Education, Economics, Accounting, and Management (ISC-BEAM), 2024)
This study aims to analyze the influence of stress management and public speaking on the academic achievement of students. This research was conducted using a quantitative method, with a sample of 35 students with accidental sampling. Data were collected through structured questionnaires and analyzed using multiple linear regression techniques. The results of the study show that Stress Management and Public Speaking, can influence the dependent variable, namely Academic Achivement, by 42,2%, while other variables outside this study influence the remaining 57,8%. The implications of this study are the importance for students to improve their stress management and public speaking skills. This can be done by attending training or seminars, as well as by practicing stress management and public speaking techniques in daily life.